Columnar mesomorphism from a new luminescent thiazolo[5, 4-d]thiazole-based core. Issue 2 (26th January 2021) - de S. Santos, Arthur B.; Girotto, Edivandro; Salla, Cristian A.M.; Malvestiti, Ivani; Falcão, Eduardo H L; Bechtold, Ivan H.; Gallardo, Hugo
ABSTRACT: Two new mesogenic compounds having a bicyclic aromatic thiazolo[5, 4-d]thiazole linked to four 1, 3, 4-oxadiazol heterocycles were synthesised and their liquid-crystalline properties were investigated. The compounds exhibit enantiotropic hexagonal columnar mesophase with strong homeotropic orientation induced under confinement, and a wide mesophase range. The molecular packing is preserved at room temperature, especially the π-stacking inside the columns, which is essential for good charge carrier transport. They show high thermal stability, blue photoluminescence in solution, and blue-green in thin film. The morphology of spin-coated films is smooth even after thermal annealing, where large molecular-ordered domains were induced, but preserving the photoluminescence quantum yield. All characteristics suggest that this new class of mesogenic molecules is promising for technological applications. Graphical abstract: uf0001